An Implication of Bilateral Investment Treaty in Protecting Foreign Direct Investment in Nepal - Khadka, Anup (KDCBAR Law Journal, 2025)
Foreign Direct Investment and Bilateral Investment Treaty are very much closely related with each other. The Modern world is much concerned about the promotion and protection of foreign direct investment so do the BIT as well. Foreign Direct Investment or FDI is a kind of investment that makes profit or interest in enterprises which works outside of the domestic territory of the investor. It is known that FDI is beneficial to both the investors and the Investment seeking Nations. Not only developing nations like Nepal, but also developed nations like USA, France, UK, Japan etc., have formulated different policies to entice Foreign Direct Investment from the nations. Foreign Direct Investment brings money, skill and technology with it. Some nations like India, China, Russia, USA are using foreign direct investment as a tool to initiate their international relations with other nations and use them in international when needed. BIT is important tool for foreign investment. Fair and Equitable Treatment, Full Protection and Security, Most Favored Nation, National Treatment, Expropriation, Compensation for Losses and Settlement of Investment Disputes are the major structure and contents of BIT which fosters and protects the foreign direct investment in least developing countries like Nepal.